Analysis Of The Implementation Of Basic Living Assistance In The Community Handled By PSC 119 Mimika - Ferdynand , Ferdynand; Rahmat Supriyatna (Sean Institute, 2024)
Mimika is one of the regency in Indonesia that has a fairly high death rate, this indicates that there is a need to implement basic life support so that people have knowledge of the application of Basic Life Assistance (BHD). The research design used in this research is mixed methods research. with a cross-sectional approach. Data processing techniques through interviews and distributing questionnaires. The population and sample in this research are the community in Mimika Regency and the Public Safety Center (PSC) in Mimika Regency. Qualitative data analysis techniques include data reduction, data presentation and drawing conclusions. Quantitative analysis techniques are carried out using classical assumption tests, multiple linear regression analysis techniques and hypothesis testing. The results of this research indicate that the effectiveness of implementing Basic Life Assistance (BHD) by the Public Service Center (PSC) in providing basic life assistance services to the community in Timika City includes; (1) Training and Certificates, (2) Accessibility and Availability of Equipment, (3) Community Socialization and Education, (4) Monitoring and Evaluation, (5) Cooperation and Partnership. The role of the community is an important key in supporting the effectiveness of the implementation of Basic Life Support (BHD) by the Public Service Center (PSC) in Timika City. (1) Active participation in BHD training, (2) Becoming a volunteer, (3) Disseminating information, (4) Providing moral support, and (5) Providing input and feedback. Responsiveness factor has no influence but Reliability (X2), Communication (X3), Skill (X4) influences the application of basic life support (Y)by PSC in providing Basic Life Assistance services for the Community in Timika City. Knowledge and knowledge influence the implementation of Basic Life Support (Y) in the community in Timika City.